Detection of lasB Gene of Pseudomonasaeruginosa Causing Different Infection - Al-Shwaikh, Rana M Abdullah; Al-Arnawtee, Abbas Falih (Al-Nahrain Journal of Science, 2019)
The result obtained 75 isolate of Pseudomonasaeruginosa included: 28 isolates from otitis media, 23 isolates from burn infections, 10 isolates from wound infections, 8 isolates from urinary tract infections and 6 isolates from blood. The isolates were identified by culturing on MacConkey agar, Blood agar, Cetrimide agar, Pseudomonas agar and CHROMagar Orientation then identified by performing biochemical tests including (oxidase test and catalase test) and further identification by using a API20E system. The result obtained Pseudomonasaeruginosa that have Las B included : 23 isolates from otitis media 82.14%, 19 isolates from burn infections 82.60%,10 isolates from wound infections 100%, 5 isolates from urinary tract infections 62.5 % and 6 isolates from blood 100%.The result revealed that the lasB gene was present in 63 isolates 84% of Pseudomonasaeruginosa. The gel electrophoresis showed that the molecular weight of alg D gene was 300bp.